Convective heat transfer enhancement with graphene nanoplatelet/platinum hybrid nanofluid. (November 2017) - Yarmand, Hooman; Zulkifli, Nurin Wahidah Binti Mohd; Gharehkhani, Samira; Shirazi, Seyed Farid Seyed; Alrashed, Abdullah A.A.A.; Ali, Mohamad Azlin Bin; Dahari, Mahidzal; Kazi, S.N.
Abstract: The work here looked into heat transfer performance in addition to friction loss of graphene nanoplatelet (GNP) - Platinum (Pt) hybrid nanofluids. The experiments were performed with non-changing limit parameters of heat-flux. Nanofluid movement was turbulent at a weight percentage ranging between 0.02 and 0.1%, with the Reynold number from 5000 to 17, 500. The experimental findings revealed that compared with the base liquid, all nanofluid samples had higher heat transfer abilities. Nusselt number elevation and the increment of the heat transfer coefficient were found to be dependent on Reynold number, and the weight concentration of the nanocomposite. The greatest value recorded for Nusselt number was 28.48%, accompanied by a 1.109-fold penalty. There was a rise in friction factor with regards to the highest load of nanocomposite (0.1 wt%), with the Reynolds number of 17, 500.